2020
DOI: 10.1088/1742-6596/1529/4/042045
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant Validity Assessment of Religious Teacher Acceptance: The Use of HTMT Criterion

Abstract: This study was conducted to produce empirical evidence of validity and reliability of a set of questionnaire. Questionnaire drawn from the results of previous studies and the validity of the tests will determine whether all aspects of the construct domain were represented, thus ensuring the high objectivity level of the questionnaire. In addition, an alternative approach was used to assess the discriminant validity, using heterotrait-monotrait ratio of correlations. The study empirically proves that the questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 16 publications
1
38
0
2
Order By: Relevance
“…Moreover, HTMT has been shown to achieve higher specificity and sensitivity rates (97% -99%) when compared to crossloadings (0.00%) and Fornell and Larcker's criteria (20.82%) (Ab Hamid et al, 2017). Specifically, discriminant validity may be tested by comparing the HTMT values of two constructs, where the HTMT value of two components should ideally be less than 0.85, but can reach as high as 0.90 if the constructs are conceptually comparable (Henseler et al, 2015;Voorhees et al, 2016;Yusoff et al, 2020). The HTMT ratio test findings vary from 0.187 to 0.462, indicating that all constructs are independent of one another and, as a result, discriminant validity exists in this study (see Table 7).…”
Section: Discriminant Validitymentioning
confidence: 99%
“…Moreover, HTMT has been shown to achieve higher specificity and sensitivity rates (97% -99%) when compared to crossloadings (0.00%) and Fornell and Larcker's criteria (20.82%) (Ab Hamid et al, 2017). Specifically, discriminant validity may be tested by comparing the HTMT values of two constructs, where the HTMT value of two components should ideally be less than 0.85, but can reach as high as 0.90 if the constructs are conceptually comparable (Henseler et al, 2015;Voorhees et al, 2016;Yusoff et al, 2020). The HTMT ratio test findings vary from 0.187 to 0.462, indicating that all constructs are independent of one another and, as a result, discriminant validity exists in this study (see Table 7).…”
Section: Discriminant Validitymentioning
confidence: 99%
“…The results for the discriminant validity using the HTMT values are illustrated in Table 3 . It was found that the HTMT criterion for each pair of measured items was from 0.711 to 0.946, in which 6 pairs of constructs were smaller than the HTMT 0.85 criterion ( Kline, 2011 ) and 3 pairs of constructs were smaller than the HTMT 0.9 criterion ( Mat Yusoff et al, 2020 ). The results indicated that only the HTMT inference indicates discriminant validity between all construct measures.…”
Section: Resultsmentioning
confidence: 99%
“…The HTMT values are illustrated in Table 4. It was found that the cognitive and teaching presences pair indicated only the HTMT inference discriminant validity, while another two pairs of constructs were smaller than the HTMT0.9 criterion (Mat Yusoff et al, 2020).…”
Section: Reliability and Validity Analysesmentioning
confidence: 95%